High yield expression and purification of equilibrative nucleoside transporter 7 (ENT7) from Arabidopsis thaliana - Girke, Christopher; Arutyunova, Elena; Syed, Maria; Traub, Michaela; Möhlmann, Torsten; Lemieux, M. Joanne (Biochimica et biophysica acta, 2015)
Equilibrative nucleoside transporters (ENTs) facilitate the import of nucleosides and their analogs into cells in a bidirectional, non-concentrative manner. However, in contrast to their name, most characterized plant ENTs act in a concentrative manner. A direct characterization of any ENT protein has been hindered due to difficulties in overexpression and obtaining pure recombinant protein. The equilibrative nucleoside transporter 7 from Arabidopsis thaliana (AtENT7) was expressed in Xenopus laevis oocytes to assess mechanism of substrate uptake. Recombinant protein fused to enhanced green fluorescent protein (eGFP) was expressed in Pichia pastoris to characterize its oligomeric state by gel filtration and substrate binding by microscale thermophoresis (MST). AtENT7 expressed in X. laevis oocytes works as a classic equilibrative transporter. The expression of AtENT7-eGFP in the P. pastoris system yielded milligram amounts of pure protein that exists as stable homodimers. The concentration dependent binding of purine and pyrimidine nucleosides to the purified recombinant protein, assessed by MST, confirmed that AtENT7-eGFP is properly folded. For the first time the binding of nucleobases was observed for AtENT7. The availability of pure recombinant AtENT7 will permit detailed kinetic and structural studies of this unique member of the ENT family and, given the functional similarity to mammalian ENTs, will serve as a good model for understanding the structural basis of translocation mechanism for the family. •AtENT7 acts as a classic equilibrative transporter.•AtENT7 was overexpressed in the P. pastoris system.•Purification of AtENT7 yielded milligram amounts of pure, stable transporter.•Purified AtENT7 was able to bind nucleosides, indicating a proper fold.•The binding of nucleobases was shown for the first time for AtENT7.